A Community-Partnered Approach to Inform a Culturally Relevant Health Promotion Intervention for Stroke. (October 2018) - Eisenstein, Amy R.; Song, Sarah; Mason, Maryann; Kandula, Namratha R.; Richards, Christopher; Aggarwal, Neelum T.; Prabhakaran, Shyam K.
Background . The purpose of this study was to generate information from multiethnic, high-risk communities to inform the creation of culturally relevant health promotion intervention for increasing early hospital arrival after stroke. Methods . The study employed a qualitative design, using focus groups with African American, Caucasian, and Hispanic adults in two Chicago community areas. The study relied heavily on stakeholder input in creating the focus group guide, recruiting participants, and interpreting the analysis. Results . Six focus groups gained information from 51 participants, including insights and perspective on participants' stroke experience and knowledge as well as on facilitators and barriers to calling 9-1-1. Qualitative analysis uncovered themes relating to risk factors, symptoms, knowledge of stroke mechanisms, experience of acute stroke, help seeking, stroke education, recovery, treatment, and emotions. Communities were closely aligned in their knowledge of stroke, but had differing ideas around stroke education and dissemination of education. Discussion . This study identified nuances in real-world barriers to receiving acute stroke services in minority and disadvantaged communities in Chicago neighborhoods. Our findings indicated significant amount of variation by race/ethnicity and, in particular, a lack of similarities based on race/ethnic groups in different communities. These findings underscore the importance of working with communities to fully understand the community-level dynamics that occur.